2021
DOI: 10.1101/2021.11.10.468148
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RPRM negatively regulates ATM levels involving its phosphorylation mediated by CDK4/CDK6

Abstract: Sensitizing cancer cells to radio- and chemotherapy remains a hot topic in cancer treatment. Here it is identified that Protein Reprimo (RPRM) negatively regulates the levels of ataxia-telangiectasia mutated (ATM) protein kinase, a master regulator of DNA damage response (DDR) in the presence of DNA double-strand breaks (DSBs), resulting in impaired DNA repair efficiency and enhanced cellular sensitivity to genotoxic agents. Mechanistically, although RPRM is primarily located in cytoplasm, it rapidly transloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 54 publications
(106 reference statements)
2
9
0
Order By: Relevance
“…This suggested that RPRM deletion protected HSCs by promoting the NHEJ repair machinery. Along with our previous finding that RPRM negatively regulates ATM (Zhang et al, 2021), this result confirms the importance of RPRM in DDR. In addition to promoting DNA repair, RPRM deletion enhanced the self‐renewal and proliferation of HSCs, which also contributed to the protective effect of RPRM deletion on HSCs after exposure to irradiation.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This suggested that RPRM deletion protected HSCs by promoting the NHEJ repair machinery. Along with our previous finding that RPRM negatively regulates ATM (Zhang et al, 2021), this result confirms the importance of RPRM in DDR. In addition to promoting DNA repair, RPRM deletion enhanced the self‐renewal and proliferation of HSCs, which also contributed to the protective effect of RPRM deletion on HSCs after exposure to irradiation.…”
Section: Discussionsupporting
confidence: 91%
“…RPRM expression can be induced by IR (Ohki et al, 2000; Zhang et al, 2021). Moreover, our previous results showed that RPRM‐knockout mice were more radioresistant and survived longer than WT mice after exposure to X‐ray irradiation (Zhang et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations